Knowledge, Attitudes, and Behavior to Prevent Transmission of Toxoplasma gondii among Cat Owners - Nurseha, Fajar Taufik; Mashuri, Yusuf Ari; Pamungkasari, Eti Poncorini; Maulani, Utiya Nabila (Al-Sihah: The Public Health Science Journal, 2023)
Cat owners or keepers are at a heightened risk of contracting toxoplasmosis, making it crucial to take preventive measures against Toxoplasma gondii infection (T. gondii). However, there are limited studies on knowledge, attitudes, and behavior toward preventing T. gondii among cat owners. Therefore, this study aimed to investigate the relationship between knowledge, attitudes, and behavior in preventing T. gondii infection among cat owners. To achieve this objective, an analytical observation was conducted using a cross-sectional approach. An online questionnaire was given to cat owners through social media platforms such as Facebook, Twitter, and WhatsApp. Knowledge, attitudes, and behavior of 388 respondents were evaluated using the Spearman Correlation Test. The results showed positive correlations between knowledge and attitudes (r=0.105, p<0.038), knowledge and behavior (r=0.141, p<0.006), as well as attitudes and behavior (r=0.682, p<0.001), towards preventing T. gondii. This study indicated significant associations between knowledge, attitudes, and behavior, and highlighted the importance of continuous health promotion and prevention efforts in addressing toxoplasmosis, warranting further study involving wider and larger populations.